ANALISIS KREATIVITAS SISWA SMK DALAM MATAPELAJARAN APLIB BERBASIS PROJECT BASED LEARNING (PjBL) - Halwati Najwa (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This research discusses the importance of education in developing students' potential, especially in Vocational High Schools (SMK) with a focus on the Building Modeling and Information Design (DPIB) department which teaches Building Interior Software Applications (APLIB) using the Sketchup application. The aim of the research is to overcome the low scores in the APLIB subject which are thought to be caused by students' lack of creativity in using the Sketchup application. The method proposed to increase student creativity is Project Based Learning (PjBL), which places students at the center of learning and encourages them to work independently in solving tasks or problems. The results of the literature review show that PjBL can increase student creativity by promoting understanding, students' ability to solve problems, use of media, and creativity in creating products. PjBL can also increase student involvement in learning and help them become autonomous and independent learners. Apart from that, the implementation of PjBL is expected to help vocational school students produce creative ideas using the Sketchup application and improve their abilities in solving problems and optimizing media use. This research concludes that the application of Project Based Learning (PjBL) in vocational education, especially in the context of using the Sketchup application and developing building interior design skills, can have a positive impact in improving students' creative thinking abilities